Usefulness of the Thai modified functional living index--cancer (T-FLIC) and the Thai modified quality of life index (T-QLI) for advanced non-small cell lung cancer - Thongprasert S. (2014)
Serial assessment of Karnofsky performance status (KPS), the Thai modified Functional Living Index Cancer (T-FLIC) and the Thai modified Quality of Life Index (T-QLI) have been used to estimate the quality of life of advanced non-small cell lung cancer patients. This is a prospective randomized trial of best supportive care (BSC) versus best supportive care plus combination chemotherapy given to patients with Stage III b or IV, ECOG 0-1 or 2. There was a good correlation between Karnofsky performance status (KPS) and T-FLIC scores, between T-FLIC and T-QLI scores as the study began. Thus the T-FLIC and T-QLI were useful instruments for the quality of life assessment in Thai patients.